Social representations of the earthquake disaster among those affected in the city of Lattakia - حيدر, ربا (Latakia University Journal - Arts and Humanities Sciences Series, 2024)
The current research aims to identify the social representations of the earthquake disaster among a sample of those affected living in shelter centers in the city of Latakia, identify its content from a central core and a peripheral system. The researcher adopted the descriptive approach, and the research sample consisted of (41) children (males and females) from the city of Latakia. The researcher used the associative grid technique prepared by De Rosa (1995). The research results showed that the polarity coefficient was negative at a rate of (72.41%), and the neutrality coefficient was weak at a rate of (87.80%). The results also showed that the word (fear) represents the nucleus of the centrality of representations, and the elements of the primary peripheral system included the words: (destruction of homes, anxiety, escape, sadness, shelter), and the elements of the secondary peripheral system included the words: (death, earthquake, damage, evacuation, aid humanity).